Innovations in the Bidding Law and Bidding Controversy - Santos, Laércio José Loureiro dos (Editora Dialética, 2024)
Our intention is to follow both the English and the German paradigms, that is, to work in an accessible language (an English tendency) and to think problems through, like Germans do.